Web site and information system for idaman realty / Lavania Gopal Krishnan - Lavania, Gopal Krishnan (2001)
I have chosen this topic of designing a web site for a real estate company as my project. This system which will be developed will give idaman realty an opportunity to have their own web site, whereby they can conduct business and attract customer to their company. This project is done in 2 part, WXET 3181 and WXET 3182. WXET 3181 will involve the system's proposal and documentation. While WXET 3182 will involve designing, implementing, testing and evaluating the system. This project is done as part of fulfilling the requirements for a Bachelor's Degree in Information Technology. I hope this system will benefit idaman realty and also to increase my knowledge in developing a system as well as understanding the real estate business. I wish to express my appreciation to all who have had a part in making this project a success.